First molecular detection of Eimeria spp. in domestic goats from Java Island, Indonesia - Dias Aprita Dewi; Yudhi Ratna Nugraheni; Aan Awaludin; Vika Ichsania Ninditya; Dwi Priyowidodo; Raden Wisnu Nurcahyo; Fitrine Ekawasti; Joko Prastowo (Open Veterinary Journal)
Background: Coccidiosis caused by Eimeria species (spp.) is a significant global health concern in goats leading to gastrointestinal illness. This condition causes clinical manifestations, including weight loss and diarrhea, resulting in worldwide economic losses. Subclinical symptoms can manifest during Eimeria infection. Neglecting this disease can lead to severe morbidity and mortality. Therefore, addressing caprine coccidiosis is imperative.